The Making of the Humanities, Volume III. The Modern Humanities - Maat, Jaap; Bod, Rens; Weststeijn, Thijs (Amsterdam University Press, 2014)
This comprehensive history of the humanities focuses on the modern period (1850-2000). The contributors, including Floris Cohen, Lorraine Daston and Ingrid Rowland, survey the rise of the humanities in interaction with the natural and social sciences, offering new perspectives on the interaction between disciplines in Europe and Asia and new insights generated by digital humanities.